The Early Impact of the COVID-19 Lockdown on Stress and Addictive Behaviors in an Alcohol-Consuming Student Population in France - Flaudias, Valentin; Zerhouni, Oulmann; Pereira, Bruno; Cherpitel, Cheryl J.; Boudesseul, Jordane; de Chazeron, Ingrid; Romo, Lucia; Guillaume, Sébastien; Samalin, Ludovic; Cabe, Julien; Bègue, Laurent; Gerbaud, Laurent; et al. (Frontiers in Psychiatry, 2021)
Background. This study evaluated factors linked with perceived stress related to the COVID-19 pandemic and lockdown and addictive behaviours prior to and during lockdown in a sample of students who indicated engaging in alcohol consumption behaviours before lockdown. Methods. Cross-sectional study. French students from four universities participated in this study, and 2760 students reported alcohol use. During the first week of lockdown, students reported their perceived levels of stress regarding COVID-19. Substance use and addictive behaviours were reported before and during lockdown, and media exposure, demographical, living conditions and environmental stressors were reported during lockdown. Results. Women reported greater levels of stress (95% CI: 1.18 to 1.93, p < 0.001). Highly-stressed students also report less social support (95% CI: -1.04 to -0.39, p < 0.001) and were more likely to worry about the lockdown (95% CI: 0.27 to -0.65, p < 0.001). Alcohol-related problemswere more prevalent among the most stressed students (95% CI: 0.02 to 0.09, p = 0.004) as well as eating problems (95% CI: 0.04 to 0.36, p = 0.016) and problematic internet use (95% CI, 0.06 to 0.14, p < 0.001). Students reporting the highest levels of stress also indicated more compulsive eating during the previous seven days (95% CI, 0.21 to 1.19, p = 0.005). Conclusions. The level of stress was strongly related to four categories of variables: (i) intrinsic characteristics, (ii) social, study and economic situation, (iii) COVID-19 exposure (by media or direct) and (iv) addictive behaviours before and during the lockdown. Several variables linked to COVID-19 were not directly linked with perceived stress, while perceived stress was found to correlate with daily life organization-related uncertainty and anticipated consequences of lockdown. Importantly, social support seems to be a protective factor on high level of stress.